Consciousness Energy Healing Treatment: Impact on the Physicochemical and Thermal Properties of Pyridoxine HCl - Nayak Gopal; Kumar Trivedi Mahendra; Branton Alice; Trivedi Dahryn; Jana Snehasis (International Journal of Nutrition, 2019)
Pyridoxine HCl plays an important role in the human body as a coenzyme in the synthesis process of amino acids and neurotransmitters such as serotonin, norepinephrine, aminolevulinic acid, sphingolipids, etc. The objective of this study was to determine the effect of the Trivedi Effect®-Consciousness Energy Healing Treatment on the various physicochemical and thermal properties of pyridoxine HCl using various analytical techniques such. The study plan involved dividing the pyridoxine HCl sample into two parts, in which, the first part was not given any treatment (control sample), while the second part was provided the Consciousness Energy Healing Treatment by a renowned Biofield Energy Healer, Gopal Nayak and named as the Biofield Energy Treated pyridoxine. The particle size values of the treated pyridoxine was altered by -19.51% (d10), -11.92% (d50), 2.46% (d90), and -2.44% D(4,3); whereas, the surface area was significantly increased by 18.92%, compared to the control sample. The powder X-ray diffraction data showed the remarkable increase in the peak intensities and crystallite sizes of the treated pyridoxine in the range from 8.81% to 21.57% and 9.64% to 17.85%, respectively compared to the control sample. Moreover, the treated pyridoxine also showed an increase in the average crystallite size by 13.69%, compared to the control sample. The total weight loss of the treated pyridoxine was significantly reduced by 13.35% during the thermal degradation; however, the residue weight was increased by 29.48% after degradation, in comparison to the control sample. The maximum thermal degradation temperature of the treated pyridoxine corresponding to 1st and 2nd peak was altered by 4.37% and 2.24%, respectively than the control sample. The latent heat of fusion of the treated pyridoxine was significantly increased by 5.89% compared to the control sample. Hence, it was assumed that the Trivedi Effect®-Consciousness Energy Healing Treatment might form a new polymorph of pyridoxine HCl that might be helpful in designing more efficacious pharmaceutical/nutraceutical product due to its better solubility, absorption, bioavailability, and thermal stability than the untreated sample.
Keywords: Pyridoxine HCl